2002
DOI: 10.1097/01.mp.0000028572.44247.cf
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Thyroid Transcription Factor-1 in Normal and Neoplastic Lung Tissues

Abstract: The expression of thyroid transcription factor-1 in normal and neoplastic tissues and cell lines of the human lung was investigated using immunohistochemistry and in situ hybridization in conjunction with reverse transcription polymerase chain reaction. In normal lung tissues, immunoproducts of thyroid transcription factor-1 were observed in the nuclei of alveolar cells and bronchiolar cells. Interestingly, in distal bronchioles, immunohistochemistry and in situ hybridization revealed that thyroid transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
69
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 29 publications
(38 reference statements)
2
69
0
3
Order By: Relevance
“…[68][69][70] Subsequent investigations using the 8G7G3/1 monoclonal antibody, however, have shown that TTF-1 expression is usually absent in these tumors. 47,[71][72][73][74][75] In the present investigation, none of the squamous carcinomas of the lung or the mesotheliomas exhibited TTF-1 positivity. While these findings indicate that TTF-1 immunostaining is not useful in discriminating between these malignancies, it may have some utility in distinguishing squamous carcinomas from lung adenocarcinomas since this marker is often expressed in the latter tumors.…”
Section: Discussionmentioning
confidence: 81%
“…[68][69][70] Subsequent investigations using the 8G7G3/1 monoclonal antibody, however, have shown that TTF-1 expression is usually absent in these tumors. 47,[71][72][73][74][75] In the present investigation, none of the squamous carcinomas of the lung or the mesotheliomas exhibited TTF-1 positivity. While these findings indicate that TTF-1 immunostaining is not useful in discriminating between these malignancies, it may have some utility in distinguishing squamous carcinomas from lung adenocarcinomas since this marker is often expressed in the latter tumors.…”
Section: Discussionmentioning
confidence: 81%
“…8 Others have also reported high frequencies (generally 485% of cases) of TTF-1 expression by pulmonary small cell carcinomas as well as many pulmonary adenocarcinomas. 9,[12][13][14][15][16][17][18][19] Interestingly, in two of our original cohort of cases, observation of TTF-1 staining, in combination with a lack of p63 and high molecular weight keratin staining, led to reconsideration of the diagnosis, additional mucicarmine and surfactant precursor protein B staining, and reclassification. TTF-1 is a transcription factor that is normally expressed in alveolar pneumocytes, Clara cells, ciliated respiratory epithelial cells, and basal cells of the lung, 9 and is also expressed in the thyroid and brain.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Recent studies suggest the potential utility of several newer antibodies including thyroid transcription factor-1 (TTF-1), p63, p16(INK4A) (p16), and high molecular weight keratin, to help differentiate between small cell carcinomas and non-small cell carcinomas. [7][8][9][10] In this study, we evaluated the utility of a panel of these antibodies for distinguishing between small cell carcinoma and poorly differentiated squamous cell carcinoma.…”
mentioning
confidence: 99%
“…10 It has been primarily used for distinguishing lung carcinomas, both primary and metastatic, from other carcinomas. MOC-31 is a membrane glycoprotein isolated from a lung small cell carcinoma cell line, which has been shown to stain most normal epithelium and the vast majority of carcinomas.…”
mentioning
confidence: 99%